KAMPANYE PEMILU DILEMBAGA PERGURUAN TINGGI SEBAGAI SARANA PENDIDIKAN POLITIK (ANALISIS PASCA PUTUSAN MK NO 65/PUU-XXI/2023 - Hendrawan; Farhanuddin, Farhanuddin (Universitas Sulawesi Barat, 2023)
The aim of this research is to analyze electoral campaigns in higher education institutions as a means of political education after the decision of the Constitutional Court No. 65/PUU-XXI/2023. This research method uses library research, which is a method of collecting data by also understanding and studying the principles and theories of various research-related literatures. The results of this research show that electoral campaigns in higher education institutions have sparked various controversies. Many academics, practitioners and the general public have welcomed this new development as campus campaigns can have positive potential or impacts such as empowering students, encouraging social change. , developing understanding and skills. But many of them also protested and forcefully rejected the existence of campus or university campaigns for various reasons, including campus operational activities that could be disrupted. The rejection of campus organizations that did not conform to the vision and ideas held by certain political parties.